Implementation of Role-Play Based Demonstration Methods in Arabic Learning in Class IX Madrasah Tsanawiyah N 2 Pemalang - Akhmad Aufa Syukron; Malikha Fatikhaturrohmah (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2026)
The aims of this study is to describe the Implementation of the Arabic Learning with role-play based Demonstration Method at Madrasah Tsanawiyah Negeri 2 Pemalang Class IX and describe the obstacles and solutions in the Implementation of Arabic Language Learning Using the Demonstration Method in Madrasah Class IX Tsanawiyah Negeri 2 Pemalang. This research uses a qualitative approach with a type of field research. Data collection techniques use observation, interviews, and documentation. The data analysis carried out is data reduction, data analysis, and conclusions drawn. The results of the study show that the application of the role-play based demonstration method in Arabic learning in grade IX Madrasah Tsanawiyah Negeri 2 Pemalang can make students more confident in speaking Arabic in class, students are able to pronounce and memorize Arabic vocabulary and data play an active role in learning. Internal factor constraints: limited supporting media. External factors: lack of interest in learning Arabic, environment, and different characteristics. Internal factor solution: leveraging existing technology. External factors: motivate and interest students to learn and pay more attention.